EFEKTIVITAS PENYUSUNAN BAHAN AJAR BERBASIS WEBSITE PADA PENGEMBANGAN KOMPETENSI WIDYAISWARA BERJENJANG - Saeful Nurdin (Balai Diklat Keagamaan Bandung, 2018)
The purpose of this study to determine the effectiveness of the preparation of web-based teaching materials exelearning as a new curriculum, with a quantitative descriptive method. Web-based authoring application program known as eXe (the elearning xhtml editor) is an open source program developed and easy to use by people who do not understand html programming language though, this application can be opened through the application android mobile phone or leptop with internet protocol (IP) address or IP address without bandwidth. The new curriculum is expected to enrich the creative and interactive classroom learning, the research results obtained average score of competence test 47.27, the effectiveness percentage of 54.54% with high category, 18.18% with high enough category, and 27.30% low category.Key words : effectiveness, teaching material, exelearning